2012
DOI: 10.1159/000338411
|View full text |Cite
|
Sign up to set email alerts
|

Aging and Diets Regulate the Rat Anterior Pituitary and Hypothalamic Transcriptome

Abstract: Dietary interventions involving caloric restriction represent a powerful strategy to prevent or delay age-related deteriorations and diseases. Their beneficial effects have been observed in several tissues and species. This microarray study investigated the effects of aging, long-term moderate caloric restriction (LTMCR) and long-term dietary soy on the regulation of gene expression in the anterior pituitary and hypothalamus of 20-month-old Sprague-Dawley rats. In both tissues, aging regulated genes mainly inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 60 publications
2
5
0
Order By: Relevance
“…45 Enhanced ghrelin signaling improved the levels of neuronal genes involved in inflammation, apoptosis, DNA repair and migration in the hypothalamus of klotho-deficient mice. These findings are consistent with previous reports in which the beneficial effect of CR on age-related hypothalamic gene changes 46 and the neuroprotective effect of ghrelin 47 were observed. Cancer and dementia are the most debilitating conditions associated with aging.…”
Section: Discussionsupporting
confidence: 94%
“…45 Enhanced ghrelin signaling improved the levels of neuronal genes involved in inflammation, apoptosis, DNA repair and migration in the hypothalamus of klotho-deficient mice. These findings are consistent with previous reports in which the beneficial effect of CR on age-related hypothalamic gene changes 46 and the neuroprotective effect of ghrelin 47 were observed. Cancer and dementia are the most debilitating conditions associated with aging.…”
Section: Discussionsupporting
confidence: 94%
“…In fact, diabetes has been associated with declining cognitive performance in aging (Umegaki et al, 2013), and elevated levels of circulating glucose and insulin, as found in OAL SD rats, are prevented by LTCR (Bedard et al, 2010). In AL male SD rats, aging was associated with a large BW gain as previously reported (Bedard et al, 2010, 2013; Moyse et al, 2012). In 20-month-old AL rats, BW was 216% higher than in YAL rats, and LTCR prevented this increase [Figure 3A, One-Way ANOVA, F (2, 21) = 73.49, p < 0.0001, n = 5–11].…”
Section: Resultssupporting
confidence: 77%
“…Rats had free access to chow, except for CR rats, and water. At 7.5 months, SD rats were subjected or not to 20% caloric restriction for 2 weeks and 40% thereafter until death (Bedard et al, 2010, 2013; Moyse et al, 2012). AL and CR SD rats were fed chow Teklad control diet TD04088 and fortified TD 04089, respectively, to ensure that the two groups receive equivalent amounts of minerals and vitamins (Harlan Teklad, Madison, WI), as previously described (Moyse et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This last element is extremely important to understand the establishment and the development of obesity by studying key molecular signals at different steps and reveal the underlying paths. Importantly, the data generated on preferentially expressed genes in the hypothalamus and pituitary gland [ 125 , 126 ] improve the understanding of the central control of energy metabolism and diet impact on gene expression.…”
Section: Diet-related Genes: a Focus On High-fat Diet To Identify mentioning
confidence: 99%